Optimalisasi Peran Amil Zakat Resmi dalam Meningkatkan Transparansi dan Akuntabilitas Pengelolaan Zakat di Desa Mojopuro - Dina Rustiani Agustina; Fauzun Jamal; Farid Kamal; Adinda Puteri Andris (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Zakat management at the village level requires a high level of transparency and accountability to increase public trust and the effectiveness of distribution to mustahik. This study aims to analyze the optimization of the role of official zakat administrators in strengthening zakat management in Mojopuro Village. The research method used a seminar and mentoring approach, involving prospective amil, village officials, and religious and community leaders to improve understanding of regulations, reporting, and coordination of zakat management. The results of the study show that the establishment of official zakat amil, supported by accountability training and cross-stakeholder collaboration, changed zakat management practices from informal to systematic, documented, and transparent. This transformation had an impact on increasing participants' understanding, community trust, and a significant growth in the number of mustahik beneficiaries. In conclusion, optimizing the role of official zakat administrators through education, training, and institutional support is key to building professional, accountable, and sustainable zakat management at the village level, which can also be used as a model of good practice for other villages in Indonesia.